Pengaruh Penggunaan Mobile Banking, Transaksi Qris, dan Total Pengguna terhadap Pertumbuhan Aset Perbankan Syariah - Abeng Suhendra; Femei Purnamasari; Muhammad Iqbal Fasa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study analyzes the effect of mobile banking usage, QRIS transactions, and the total number of digital service users on Islamic banking asset growth in Indonesia. The research is motivated by increasing digital banking activities not matched by optimal asset growth, requiring empirical testing to assess digitalization effectiveness on financial performance. A quantitative approach with a causal design is employed. Data consist of secondary time-series data for 2023–2025 obtained from official publications of the Financial Services Authority (OJK) and Bank Indonesia (BI). The sampling technique uses census sampling, selecting the entire population due to limited observations and high relevance. Data analysis applies multiple linear regression using SPSS, including classical assumption tests: normality, multicollinearity, autocorrelation, and heteroscedasticity. Results show that, partially, mobile banking usage has a positive, significant effect on asset growth (sig 0.008 < 0.05), QRIS transactions show a positive, significant effect (sig 0.047 < 0.05). The total number of users does not significantly affect asset growth (sig 0.722 > 0.05). Simultaneously, all variables significantly influence asset growth (sig 0.007 < 0.05). The coefficient of determination (R²) is 0.188, indicating 18.8% of asset growth variation is explained by the independent variables, while 81.2% is influenced by factors outside the model. These findings indicate digitalization through mobile banking and QRIS supports asset growth. However, increasing user numbers alone does not significantly impact growth without improving usage quality and optimizing financial intermediation. Integration of digital services with fund mobilization and financing strategies is essential to achieve sustainable asset growth.